2018
DOI: 10.5432/jjpehss.17051
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between active drag in front-crawl and passive drag on the body with a streamlined position at various velocities

Abstract: The purpose of this study was to compare active drag during front-crawl swimming performed by competitive swimmers with passive drag acting on the same group of swimmers with a streamlined position at various velocities. Seven male competitive swimmers participated in this study, and the testing was conducted in a swimming flume. Active drag was evaluated for front-crawl swimming with upper and lower limb motion using a methodology that estimates the drag in swimming using measured residual thrust values (MRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, the results obtained showed that the increase in horizontal velocity was influenced by horizontal velocity at the start of OUAS, and high-level swimmers accelerated the body in a manner that was dependent on horizontal velocity at the start of OUAS. Regarding the relationship between swimming velocity and drag, Narita et al (Narita et al, 2018) suggested that the effects of active drag increased at higher swimming velocities and highlighted the importance of underwater power output at a high velocity. Although OUAS has not yet been examined as a predictor of underwater power output, the results of the present study, including the relationship between the maximum velocity of OUAS and FINA points, demonstrate the validity of the method to evaluate underwater power output, and suggest that OUAS, which alters velocity at the start of OUAS, is effective underwater power training for the back and upper limbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the results obtained showed that the increase in horizontal velocity was influenced by horizontal velocity at the start of OUAS, and high-level swimmers accelerated the body in a manner that was dependent on horizontal velocity at the start of OUAS. Regarding the relationship between swimming velocity and drag, Narita et al (Narita et al, 2018) suggested that the effects of active drag increased at higher swimming velocities and highlighted the importance of underwater power output at a high velocity. Although OUAS has not yet been examined as a predictor of underwater power output, the results of the present study, including the relationship between the maximum velocity of OUAS and FINA points, demonstrate the validity of the method to evaluate underwater power output, and suggest that OUAS, which alters velocity at the start of OUAS, is effective underwater power training for the back and upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The findings obtained revealed that wave drag has a negative effect on swimmers as swimming velocity increases (Narita et al, 2017;Tsunokawa et al, 2019;Vennell et al, 2006), and that active drag is proportional to the cube of swimming velocity (Narita et al, 2018). In addition, Narita et al (Narita et al, 2018) suggested that passive and active drag showed different changes with increases in swimming velocity and this behaviour was associated with the stroke rate. Based on this information, the methods used in these studies are extremely useful for analysing swimming techniques.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Similarly, in short-distance events at the national competition level, the difference in average swimming speed is more than 2.0 m/s. Narita et al (2018) reported that the body receives from the fluid while swimming increases in proportion to the third power of the swimming speed, suggesting that higher swimming speed environments may produce greater resistance. These results suggest that the swimming characteristics of the 50-m crawl swimmer and the 100-m crawl swimmer may differ because of the difference in swimming speed.…”
Section: Introductionmentioning
confidence: 99%